Genome stability assessment of PRRS vaccine strain with new ARTIC-style sequencing protocol - Jakab, Szilvia; Bálint, Ádám; Cseri, Karolina; Bali, Krisztina; Kaszab, Eszter; Domán, Marianna; Halas, Máté; Szarka, Krisztina; Bányai, Krisztián (Frontiers in Veterinary Science, 2024)
A tiling amplicon sequencing protocol was developed to analyse the genome sequence stability of the modified live PRRSV vaccine strain, Porcilis MLV. The backbone of the ARTIC-style protocol was formed by 34 individual primer pairs, which were divided into two primer pools. Primer pairs were designed to amplify 532 to 588 bp fragments of the corresponding genomic region. The amplicons are suitable for sequencing on Illumina DNA sequencers with available 600-cycle sequencing kits. The concentration of primer pairs in the pools was optimized to obtain a balanced sequencing depth along the genome. Deep sequencing data of three vaccine batches were also analysed. All three vaccine batches were very similar to each other, although they also showed single nucleotide variations (SNVs) affecting less than one percent of the genome. In the three vaccine strains, 113 to 122 SNV sites were identified; at these sites, the minority variants represented a frequency range of 1 to 48.7 percent. Additionally, the strains within the batches contained well-known length polymorphisms; the genomes of these minority deletion mutants were 135 to 222 bp shorter than the variant with the complete genome. Our results show the usefulness of ARTIC-style protocols in the evaluation of the genomic stability of PRRS MLV strains.